Notes on a Brass Table Clock bequeathed to the Society of Antiquaries of Scotland by the late Hugh J Rollo, W.S., and a Silver-cased Table Clock bequeathed to the Society by the late Lady Jane Dundas - Brook, Alexander J S (Proceedings of the Society of Antiquaries of Scotland, 1906)